Optimal components assignment problem for a flow network with node failure using fuzzy optimization - Hassan, M.R.; Hamdy, H.; Alkhalaf, Salem; Bahaa Eldin, Ayman M; Ahmed, Mahrous; Hemeida, A.M. (Ain Shams Engineering Journal, 2022)
The optimal components assignment problem in a flow network with node failure in the presence of system reliability and total lead-time constraints is studied in this paper. By using fuzzy membership functions, we formulated the problem as fuzzy linear optimization. Genetic optimization algorithm with fuzzy optimization is suggested for solving the presented problem. The suggested approach succeeded in finding an optimal solution that distinguishes with increasing reliability and minimizing total lead-time. The suggested technique is examined on various models, four nodes, six nodes, and eight nodes computer networks.